The mechanism of basaltic explosions: Experimental modeling - Ozerov A.Yu. (My University, 2010)
An instrument package for simulating basaltic eruptions (IPSBE) with a height of 18 m has been developed for investigating the processes that occur during Strombolian eruptions. The device follows the geometrical ratio between the actual plumbing system of a volcano, with the ratio of conduit diameter to conduit height being 1 to 1000. For the first time in physical modeling studies, we created conditions in which a moving gassaturated model liquid enters the conduit; this enabled us to study bubble nucleation, expansion, and coalescence, the generation and transformation of gas structures, and the kinetic features shown by the evolution of the gas phase. These experiments revealed a novel (previously unknown) flow pattern of two phase mixtures in a vertical column, viz., a cluster flow that involves the regular alternation of compact clusters of gas bubbles that are separated by a fluid that does not involve a free gas phase. It is shown that the liquid, bubble, cluster, and slug flow patterns are mutually transformed under certain conditions; they are polymorphous modifications of a gassaturated liquid moving in a vertical pipe. The data thus acquired suggested a new model for the gas–liquid movement of a magma melt in a conduit: depending on the type of gas–liquid flow behavior at the vent, the crater will exhibit different types of explosive activity, including actual explosions.
Keywords: 38.01.77 Методы исследования и моделирования. Математические и кибернетические методы в геологии; 38.37.25 Вулканология; Strombolian type